The Influence of Price, Relationship Marketing and Word Of Mouth on Purchase Decisions: Pengaruh Harga, Relationship Marketing dan Word Of Mouth terhadap Keputusan Pembelian - Abbas Moh Afghoni; Mudji Astuti (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the effect of price, relationship marketing and word of mouth on purchasing decisions on CV. Wonokoyo Gasindo in Beji Pasuruan. This research is a type of quantitative research with hypothesis testing. Sampling in this study was carried out by probability sampling method with the type of simple random sampling with the number of respondents as many as 100 respondents to CV consumers. Wonokoyo Gasindo. The analytical tool used is multiple linear regression analysis, classical assumption test, t test, F test, multiple correlation coefficient and multiple determination coefficient (R2) using SPSS version 25.0 application program. This primary data was obtained through a questionnaire whose measurement was using a Likert scale. And the data is declared to be valid and reliable. The results of the study prove that the price has an effect on purchasing decisions. Relationship marketing has an effect on purchasing decisions. Word of mouth has an effect on purchasing decisions. Price, relationship marketing and word of mouth have a simultaneous effect on purchasing decisions on CV. Wonokoyo Gasindo in Beji Pasuruan.